Perception of Professionals in North India on Fair Value Measurement - Navneet Kaur, (European Economic Letters (EEL), 2023)
India is one of the several nations that follow IFRS system, under which fair value approaches are used. The purpose of this report is to study and investigate how North Indian professional accountants are using the fair value approach and their perceptions regarding it. Fair value accounting has a significant influence on the reporting of financial statements and the process of decision making. This study also explores the viewpoint of professional accountants residing in North India with the help of secondary resources. The historical background of the fair value accounting concept in India and its historical background are also being explored in this research paper. The different methods of valuation are also discussed in this research paper, such as cost, income, and market approaches. The progress of fair value adoption is also being analyzed through the benefits of the concept.